Efficacy of gallium in tooth loss prevention - Aleksić Milena D.; Lukić Aleksandra M. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2016)
Introduction: Over the past three decades, gallium compounds have gained importance in medicine. Radioactive gallium and stable gallium nitrate are used as diagnostic and therapeutic agents in cancer and disorders of calcium and bone metabolism. In addition, gallium compounds have displayed anti inflammatory and immunosuppressive activity in animal models of human diseases. More recent studies have shown that gallium compounds may also function as antimicrobial agents. In the review, the potential application of gallium in the future treatment of periodontitis and prevention of tooth loss will be discussed. Gingival inflammation, bacterial infection, alveolar bone destruction and subsequent tooth loss are characteristic features of periodontal disease. Surgical techniques, mechanical debridement of the denuded root surface, and local or systemic application of antimicrobial agents are currently used treatments for periodontitis. However, the development of antibiotic resistance in bacteria has prompted a great need for new and alternative treatment methods for infection. Conclusion: The potential anti-periodontitis benefits of gallium are related to eradicating infection due to bacterial biofilms, increasing bone deposition and downregulating unwanted immune responses. Adjunctive use of gallium laser therapy with mechanical instrumentation in combination with gallium-containing gingival gels, toothpastes and mouth rinses may represent the final solutions for tooth loss prevention.